2007
DOI: 10.1109/tac.2007.899057
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of Switched Positive Linear Systems

Abstract: Abstract-It was recently conjectured that the Hurwitz stability of the convex hull of a set of Metzler matrices is a necessary and sufficient condition for the asymptotic stability of the associated switched linear system under arbitrary switching. In this note, we show that 1) this conjecture is true for systems constructed from a pair of second-order Metzler matrices; 2) the conjecture is true for systems constructed from an arbitrary finite number of second-order Metzler matrices; and 3) the conjecture is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
188
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(190 citation statements)
references
References 15 publications
1
188
0
1
Order By: Relevance
“…, A N } are the system matrices of the constituent systems, which are Metzler matrices. See [21,7] for more details on systems of this type.…”
mentioning
confidence: 99%
“…, A N } are the system matrices of the constituent systems, which are Metzler matrices. See [21,7] for more details on systems of this type.…”
mentioning
confidence: 99%
“…Moreover, there can exist system classes for which the existence of a CQLF for any pair of systems in a finite family implies the existence of a CQLF for the entire family. This was shown to be the case for the class of second order positive systems in Gurvits et al (2004). This fact provides further motivation for the study of the problem of CQLF existence for pairs of systems.…”
Section: Introductionmentioning
confidence: 65%
“…Recently, Gurvits et al [13] proved that this conjecture is in general false (see also [12]). However, they also showed that it does hold when n = 2 (even when the number of matrices is arbitrary).…”
Section: Conjecture 2 If (1) Is a Pls Then Assumption 1 Provides A Sumentioning
confidence: 99%